2005
DOI: 10.1667/rr3302
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Limits Endothelial Activation after Irradiation and Decreases the Resulting Inflammatory and Thrombotic Responses

Abstract: Endothelial dysfunction has been implicated in the pathogenesis of atherosclerosis, fibrosis and vascular occlusion after radiation therapy. Statins have been reported to improve endothelial function; however, this beneficial effect on endothelial cells has never been investigated after irradiation. Therefore, using human microvascular endothelial cells from lung that had been irradiated with 5 or 10 Gy, we assessed the effect of pravastatin on endothelial activation by ELISA, cell-ELISA and electrophoretic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 54 publications
4
63
1
4
Order By: Relevance
“…Statins exert anti-inflammatory and anti-thrombotic effects on irradiated endothelial cells in vitro (40) and reduce lung injury in mice after irradiation of the chest (41).…”
Section: Discussionmentioning
confidence: 99%
“…Statins exert anti-inflammatory and anti-thrombotic effects on irradiated endothelial cells in vitro (40) and reduce lung injury in mice after irradiation of the chest (41).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are HMG-CoA reductase inhibitors that are widely used to treat hypercholesterolemia; their potential radioprotective effects have been discussed in a limited number of preclinical and clinical studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Clinical studies have reported that pravastatin has anti-inflammatory effects and is a safe HMG-CoA reductase inhibitor that is water soluble (5).…”
Section: Discussionmentioning
confidence: 99%
“…Statins have previously been reported to have beneficial effects on radiation-induced toxicities, and numerous studies have demonstrated the anti-inflammatory effects of pravastatin following radiation exposure (7)(8)(9)(10)(11)(12)(13)(14)(15). Previous clinical data has shown that the use of statins reduces acute gastrointestinal symptoms following radical pelvic radiotherapy (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi, la pravastatine est capable, in vitro sur cellules endothéliales microvasculaires humaines, d'inhiber l'adhésion leucocytaire et plaquettaire induite par l'irradiation [15]. Une étude réalisée in vitro sur cellules endothéliales macrovasculaires humaines montre que la lovastatine protège les cellules de l'apoptose radioinduite [16].…”
Section: Quand La Cicatrisation S'emballe : De L'inflammation Aiguë àunclassified